ON THE POETICS OF ADVENTURE AND FICTION WORKS IN ENGLISH CHILDREN'S LITERATURE (Scientific journal of the Fergana State University, 2025)
This article provides detailed information about the development and research of children's literature in English literary studies. It emphasizes that children's literature has distinct research objects, often expressed through synonymous terms. The development of English children's literature from the late 18th century to the early 20th century is characterized by testing new literary styles and directions rooted in Romanticism and classical tradition. The article highlights the unique features of children's literature, the differences between children's and adult literature through genres such as fantasy and absurdism, and the role of childhood themes in the artistic process. It also notes the significance of the formation of child characters and the uniqueness of children's literature during the Romantic period, particularly in the Victorian era. Additionally, the article encompasses the specific goals and artistic elements of children's literature. In addition, information is provided about a number of scholars who are considered representatives of English children's literature. In particular, the role of Charles Dickens's "Oliver Cromwell" and Lewis Carroll's "Alice in Wonderland" and "Through the Looking Glass" in English children's literature is discussed. The artistic images of children's works such as Oliver Cromwell and Alice are analyzed from a gnoseological perspective.